Channel Improvement in Shipping at Hantipan Canal in Supporting the Transportation of River in Katingan, Central Borneo Province - Ong Argo Victoria; Bambang Setiawan; Intan Permata Sari (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2019)
Narrowing the channel by landslides and silting in the mid-section channel Of Hantipan Canal, especially during the dry season some places even just an ankle of adults, it causes the boat must be pushed or lifted in order to be able to get to the destination and causing the motor boat forced to sail past the Sampit Bay the wave height reaches 1-3 meters, there are also obstacles such as wood left alone milestone along that channel. Local communities expect their dredging activities of Hantipan Canal in order to facilitate their primary access to the other areas so that the ship does not need to pass through The Sampit Bay and can reduce accidents caused by high waves in The Sampit Bay. Dredging activities is expected to make the traffic channel becomes more smoothly although at certain points must remain aware of the occurrence of sedimentation that can make the ship got stuck and foundered.Along with it, the river transport is felt increasingly important and strategic to the advancement and development of the region, then it should be able to be improved both in terms of facilities and infrastructure.